Historical and art study, artistic and didactic researches of Miroslav Skoryk’s piano works - Ivakhova, Kateryna (Pedagogical Discourse, 2013)
The article analyses thehistorical and art study, artistic and didactic researchesof Myroslav Skorykʼs piano works as educational material for students of musical schools. It characterizes scientific publications, which highlight the genre-stylistic, figurative and thematic, performance-interpretation, artistic-didactic features of the piano works, as well as genetic, familial, regional and national prerequisites of the formation of his world outlook and musical culture. Special attention is paid to defining the role of M.Skorykʼs piano works in the traditions of national and world music culture.